The Gospel of the Ebionites and the Gospel of Luke - Edwards, James R. (New Testament studies, 2002)
Scholarly consensus generally assumes that the Gospel of the Ebionites as preserved by Epiphanius is either a harmony of the Synoptic Gospels or excerpted mainly from Matthew. A synopsis of the texts, however, demonstrates that the Epiphanius quotations show stronger affinity with Luke than with Matthew or Mark. Indeed, the evidence suggests that Epiphanius's references to the Gospel of the Ebionites are not excerpted from Luke, but rather from a Greek translation of the elusive Hebrew Gospel attested by a number of church fathers, and thus one of the sources of Luke mentioned in the prologue of his Gospel.